Religious diversity in Canadian public schools: rethinking the role of law - Dabby, Dia (Law and society series, 2022)
Everyday Law in Schools -- Litigation about Religion and Education: On (Un)Heard Voices -- Mediating Religious Diversity in Public Schools -- The Administrative Governance of Public Schools -- Relations of Belonging in Education to Mediate Diversity.